Call for papers for issue 3-2019 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The instructions to authors about the article preparation for publication in the Military Technical Courier are based on the Act on scientific journal editing of the Ministry of Science and Technological Development of the Republic of Serbia, No 110-00-17/2009-01 of 9th July 2009. This Act aims at improving the quality of national journals and raising the level of their compliance with the international system of scientific information exchange. It is based on international standards ISO 4, ISO 8, ISO 18, ISO 215, ISO 214, ISO 18, ISO 690, ISO 690-2, ISO 999 and ISO 5122 and their national equivalents.